Aplikasi Kompos Sampah Organik Berstimulator Em4 untuk Pertumbuhan dan Produksi Tanaman Jagung (Zea Mays, L.) pada Lahan Kering - Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
The aim of this experiment was to study the effects of effective microorganism 4 (EM4) stimulatory on compost quality and to test of the compost with different dosage on growth and production of corn in dry land. Randomized Complete Block Design with 4 treatment and 3 replicates was use in the experiment. The treatment of compost dosage were : 0 ton/ha, 15 ton/ha, 30 ton/ha, 45 ton/ha. The parameter observedfor compost quality were : C/N ratio, . mineral content N,P,K,Ca, Mg . Heigh and dry weigh of plant, amount of fruit and seed, dry weigh of seed were observed for growth and production of plant. The results of the experiment proved that decompose of organic matter with EM4 stimulatory increase mineral content in compost. The compost treatment on dry land increase growth and production of corn. The higher dosage until 30 ton/ha of the compost the higher of growth and production of corn. The best result of the amount of seed was found from 45 ton/ha compost treatment.